CARTOONS KILL: casualties in animated recreational theater in an objective observational new study of kids' introduction to loss of life. (16th December 2014) - Colman, Ian; Kingsbury, Mila; Weeks, Murray; Ataullahjan, Anushka; Bélair, Marc-André; Dykxhoorn, Jennifer; Hynes, Katie; Loro, Alexandra; Martin, Michael S; Naicker, Kiyuri; Pollock, Nathaniel; Rusu, Corneliu; et al.
Abstract : Objectives To assess the risk of on-screen death of important characters in children's animated films versus dramatic films for adults. Design Kaplan-Meier survival analysis with Cox regression comparing time to first on-screen death. Setting Authors' television screens, with and without popcorn. Participants Important characters in 45 top grossing children's animated films and a comparison group of 90 top grossing dramatic films for adults. Main outcome measures Time to first on-screen death. Results Important characters in children's animated films were at an increased risk of death compared with characters in dramatic films for adults (hazard ratio 2.52, 95% confidence interval 1.30 to 4.90). Risk of on-screen murder of important characters was higher in children's animated films than in comparison films (2.78, 1.02 to 7.58). Conclusions Rather than being the innocuous form of entertainment they are assumed to be, children's animated films are rife with on-screen death and murder.